Perangkat Lunak Komputer untuk Penentuan Kecukupan Asupan Gizi Makanan Indonesia - Bernadus Triono Utomo; Suparmo Suparmo; Agnes Murdiati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
A computer application program has been developed specifically for the nutritional analysis of Indonesia (traditional) foods. The program is also aimed to analyse the nutritional content of the food as percentage of nutritional dietary allowance of any person at any age, weight, and activity. Three data base sources are essential for the algorithm of the calculation, which are food composition table, recommended dietary allowance and over 350 recipes of Indonesia, traditional foods. The required input are respondent's data such as sex, age, activity, and state of growth and the kind and amount foods to be eat. The output abtaied is table of food nutritional composition, e.g. calorie, carbohydrate, protein, lipid, cholesterol, vitamins, and minerals and percentage of the daily intake. The program run under Window 95 is very friendly to apply, and written in Indonesian language, and nutritionists in food industry, catering, hotel, restaurant, fitness center, and maybe hospitals in providing nutritional information's to their customers